The Effect of Storytelling on Teaching Language Skills (Speaking, Listening and Fluency) among Second-Grade Students in Jordan - Al-khresha, Ibtsam Husain Muhamed (Journal of Educational and Psychological Sciences, 2022)
The current study aimed to identify the impact of storytelling on teaching language skills (speaking, listening and fluency) among second-grade students in Jordan, and to reveal the significance of the differences in the role of storytelling in teaching language skills (speaking, listening and fluency) among second-grade students in Jordan for the gender variable. In order to achieve, a questionnaire was developed consisting of (21) items divided into three areas (speaking, listening, language fluency), and the study sample consisted of (88) male and female students from the second grade of primary school in Zarqa Governorate schools, they were chosen by the intentional method, from Two divisions, one experimental and the other control. The study concluded that there is an effect of storytelling on teaching language skills (speaking, listening and fluency) among second-grade students, and it was found that there were no differences in the effect of storytelling on teaching language skills (speaking, listening and fluency) due to the gender variable, and the study recommended the need to direct those in charge of language education. Arabic by including the storytelling method in teaching methods and curricula, and the necessity of training first-grade teachers to use storytelling in teaching Arabic language skills.